RUSSIA AND TRADE INTEGRATION: PERSPECTIVES OF DEVELOPMENT OF ENTREPRENEURSHIP IN AGRICULTURE - Erokhin, Vasily; Ivolga, Anna (Economics of Agriculture, 2011)
International trade by agrarian production is still rather far from full liberalization despite of the progress achieved in international trade by agricultural production after carrying out within the framework of the World Trade Organization (WTO) of many negotiations rounds. Some new rules in the organizations of international trade and the new obligations which were taken up by the participant countries of WTO have opened the new questions to discuss and settle within the framework of the following negotiation rounds. The basic themes of such negotiations at the Russian introduction into WTO should become the questions of the state trade regulation, the further perfection of sanitary control rules, the further decrease of the custom duties and administrative character of tariff quotas establishment on imported agricultural production.